2019
DOI: 10.1103/physrevd.99.124042
|View full text |Cite
|
Sign up to set email alerts
|

Quasinormal modes, scattering, and Hawking radiation in the vicinity of an Einstein-dilaton-Gauss-Bonnet black hole

Abstract: Classical (quasinormal) and quantum (Hawking) radiations are investigated for test fields in the background of a four dimensional, spherically symmetric and asymptotically flat black hole in the Einstein-dilaton-Gauss-Bonnet (EdGB) theory. The geometry of the EdGB black hole deviates from the Schwarzschild geometry only slightly. Therefore, here we observe that the quasinormal spectrum also deviates from its Schwarzschild limit at most moderately, allowing for a 9% decrease in the damping rate and up to a 6% d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 90 publications
0
56
0
Order By: Relevance
“…Quasinormal modes and shadows of black holes are, apparently, among the most interesting characteristics of black holes in the gravitational and electromagnetic spectra. They have been observed in the modern experiments, still, leaving the wide room for interpretations and alternative theories of gravity [1][2][3][4][5][6][7][8][9][10][11]. A number of such alternative theories appeared in attempts to answer a number of fundamental questions which cannot be resolved with General Relativity, such as, for example, construction of quantum gravity or a e-mail: roman.konoplya@gmail.com (corresponding author) b e-mail: antonina.zinhailo@physics.slu.cz singularity problem.…”
Section: Introductionmentioning
confidence: 99%
“…Quasinormal modes and shadows of black holes are, apparently, among the most interesting characteristics of black holes in the gravitational and electromagnetic spectra. They have been observed in the modern experiments, still, leaving the wide room for interpretations and alternative theories of gravity [1][2][3][4][5][6][7][8][9][10][11]. A number of such alternative theories appeared in attempts to answer a number of fundamental questions which cannot be resolved with General Relativity, such as, for example, construction of quantum gravity or a e-mail: roman.konoplya@gmail.com (corresponding author) b e-mail: antonina.zinhailo@physics.slu.cz singularity problem.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we apply the geometrical optics approximation and assume the emitted massless quanta move along null geodesics. However, to get a precise lifetime one has to compute the grey body factors of all the particles [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. On the other hand, near the end of the evaporation, effective field theory starts to fail, and quantum gravity effect may stop the evaporation, leaving a black hole "remnant" [64][65][66][67].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This approach was used to construct the analytical approximation of numerical blackhole solutions in the Einstein-Weyl [16], Einstein-dilaton-Gauss-Bonnet [17] and Einstein-scalar-Maxwell [18] theories. Further studies of observables in these parametrized spacetimes [19][20][21][22][23][24] showed that usually it is sufficient only two-three orders of the continued fraction expansion in order to achieve reasonable accuracy.…”
Section: Introductionmentioning
confidence: 99%